Beyond pluralizing African childhoods: Introduction. (August 2016) - Abebe, Tatek; Ofosu-Kusi, Yaw
This Special Issue of Childhood moves beyond stereotypical images of African children to document the complex ways in which contemporary realities and processes of social transformations shape and are shaped by children's everyday lives. In this editorial, we bring together perspectives that are drawn from 10 articles that report findings from six countries: Zambia, Rwanda, South Africa, Ethiopia, Uganda and Ghana. The insights generated reveal the importance of looking beyond the 'deficit' model of childhood to instead theorize how children, through their engagements in social, economic, cultural and political life, contribute to the reconfiguration of social and generational dynamics that unfolds in Africa.